2019
DOI: 10.1080/19315864.2019.1636911
|View full text |Cite
|
Sign up to set email alerts
|

Attributions of People with Intellectual Disabilities of Their Own or Other Clients’ Challenging Behavior: A Systematic Review of Qualitative Studies

Abstract: Introduction: As opposed to studies focusing on staffs' attributions of challenging behavior (CB), relatively few studies have looked at how people with intellectual disabilities (ID) attribute such behaviors themselves, and a systematic overview is currently lacking. The aim of this review was to synthesize the evidence from qualitative studies on the attributions people with ID have concerning their own or other clients' CB. Methods: A systematic literature search was conducted in Embase, Medline Ovid, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…Reports based on checklists completed by families and professional caregivers may vary according to their previous experience and knowledge regarding manifestations of psychiatric disorder in this population (Kildahl et al 2017). In line with previous suggestions (Appleton et al 2019, Valdovinos et al 2019, Helverschou et al 2011b, direct observation by mental health professionals with specific knowledge and experience concerning psychiatric disorder in ASD and ID may thus be particularly important as the diagnostic complexity increases, and was helpful also in the current study. Recent findings suggest that the challenges present in assessment of psychiatric disorder in this population are present also in evaluation of treatment effects (Rysstad et al 2020), and the use of similar, multimodal strategies proved helpful for evaluation in the current case.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Reports based on checklists completed by families and professional caregivers may vary according to their previous experience and knowledge regarding manifestations of psychiatric disorder in this population (Kildahl et al 2017). In line with previous suggestions (Appleton et al 2019, Valdovinos et al 2019, Helverschou et al 2011b, direct observation by mental health professionals with specific knowledge and experience concerning psychiatric disorder in ASD and ID may thus be particularly important as the diagnostic complexity increases, and was helpful also in the current study. Recent findings suggest that the challenges present in assessment of psychiatric disorder in this population are present also in evaluation of treatment effects (Rysstad et al 2020), and the use of similar, multimodal strategies proved helpful for evaluation in the current case.…”
Section: Discussionsupporting
confidence: 61%
“…One of the atypical ways symptoms of psychiatric disorder may manifest in individuals with ASD and ID is as "challenging" behaviours, including self-injurious behaviours (SIB) (Rittmannsberger et al 2020, Painter et al 2018, Bitsika et al 2016, Rzepecka et al 2011. "Challenging" behaviours are complex social phenomena developing due to transactional processes between the individual and contextual/social factors (Wolkorte et al 2019, van den Bogaard et al 2019, Cooper 2016, Hemmings 2007, Emerson 2001. Studies investigating the views of people with ASD/ID have reported that a wide range of causes may contribute to these behaviours (van den Bogaard et al 2019), including lack of structure and clarity in their daily lives leading to feelings of fear and restlessness (Wolkorte et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clients have been found to attribute challenging behaviours to a range of situational and social factors (Van den Bogaard et al . 2019). Their views on the rise in incidents with aggression in response to drastic changes in their situation might therefore be especially informative for understanding the impact of COVID‐19 countermeasures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, people with an ID highly value direct support workers' qualities such as respect, honesty, trust, and a caring, nurturing manner (Clarkson et al 2009, Roeleveld et al 2011. People with an ID also indicate that negative interactions with support staff or feeling rejected by support staff may cause challenging behaviors (van den Bogaard et al 2019). This also asks for high quality interactions between client and direct support staff.…”
Section: Discussionmentioning
confidence: 99%